(untitled) (REMUNOM, 2025)
Objective: To analyze the nutritional status and functionality of patients undergoing breast cancer treatment between November 2022 and October 2023. Methods: A retrospective the data analysis was conducted using records of nutritional and physiotherapy indicators, it was conducted with overweight and obese female patients undergoing antineoplastic treatment for breast cancer. The tools used were ASG-PPP, FRIED, ECOG, and Karnofsky. BioEstat 5.0 software was used for trend analysis, employing the chi-square test and Fisher’s exact test. The study was approved by the Research Ethics Committee. Results: 30 women, aged 20 to 80 years, were evaluated. Of these, 63.3% underwent chemotherapy as their predominant cancer treatment, and 66.6% presented with overweight as their nutritional status. Analyzing the functional and nutritional capacity of cancer patients allows us to understand aspects such as life expectancy and quality of life, as well as the risks and benefits of cancer treatments. In this study, adequate scores on all the scales mentioned above were analyzed, and a statistical association was observed between adequate score levels and performance scales in cancer patients (p < 0.0001). When observing the ASG-PPP scale, approximately 83.3% of the women were classified as having nutritional status A, 23.3% of the women obtained level 1 through the ECOG scale, which was reflected in the KPS scale, where the majority (73.3%) had a score equal to 90% and 23.3% a score lower than 90%. Thus, it was observed that most had some functional impairment during the course of disease therapy, requiring some type of functional assistance. Conclusion/Final Considerations: The study demonstrated that most patients possessed adequate functional capacity and a satisfactory nutritional status, but that external factors and previous precedents can influence their functional and nutritional status.